Pengaruh Strategi Digital Marketing terhadap Keputusan Pembelian pada Coffee and Eatery di Mediasi Customer Trust di Kota Pontianak - Mursalin, Adi; Ariffin, Muchammad; Rawa, Ricola Dewi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The increasing use of social media has encouraged Coffee and Eatery businesses to rely on digital marketing strategies to influence consumer purchase decisions. However, empirical evidence regarding the mediating role of customer trust in this relationship remains inconsistent, particularly within small and medium-sized culinary enterprises outside major metropolitan areas. This study examines the effect of social media marketing on purchase decisions, with customer trust as a mediating variable, in the context of Coffee and Eatery businesses in Pontianak, Indonesia. Using a quantitative approach, data were collected from 110 consumers and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that social media marketing has a positive and significant effect on both customer trust and purchase decisions. However, customer trust does not have a significant effect on purchase decisions and does not mediate the relationship between social media marketing and purchase decisions. These findings suggest that, in experience-based industries, purchase decisions can be directly driven by digital marketing exposure without requiring prior trust formation. Theoretically, this study supports a contingency perspective by highlighting the limited role of customer trust as a mediating mechanism in certain consumption contexts. Practically, the findings emphasize the importance of structured and informative social media content in driving purchase behavior, while positioning trust-building strategies as more relevant for long-term relational outcomes rather than immediate purchase decisions.